2014
DOI: 10.14740/jcgo297w
|View full text |Cite
|
Sign up to set email alerts
|

HELLP Syndrome at 17 Weeks Gestation: A Rare and Catastrophic Phenomenon

Abstract: HELLP syndrome is a collection of symptoms described as hemolysis, elevated liver enzymes and low platelets. HELLP syndrome complicates 0.01-0.6% of pregnancies and can be considered a severe variant of preeclampsia. The occurrence of HELLP syndrome diagnosed before the 20th week of gestation has been most commonly reported in association with antiphospholipid antibody syndrome (APS) or triploid chromosomal anomalies. A 41-year-old primigravida was admitted at 17 weeks and 6 days gestation with hypertension, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
1
7
0
3
Order By: Relevance
“…She was anticardiolipin antibody-positive. The higher age of this patient is consistent with our case and another case of a 41-year-old primigravida with severe HELLP syndrome at GA of 17 weeks [ 11 ].…”
Section: Discussionsupporting
confidence: 92%
“…She was anticardiolipin antibody-positive. The higher age of this patient is consistent with our case and another case of a 41-year-old primigravida with severe HELLP syndrome at GA of 17 weeks [ 11 ].…”
Section: Discussionsupporting
confidence: 92%
“…The triad of HUS is classically described as thrombocytopenia, microangiopathic hemolytic anemia, and renal dysfunction. The addition of fever and neurologic symptoms makes the classic pentad of TTP [12]. In this case, a physical examination of our patient revealed hypertension but no evidence of purpura or petechia, neurologic abnormalities, or edema.…”
Section: Discussionmentioning
confidence: 70%
“…27 Without a doubt, preeclampsia manifesting before 20 weeks' gestation is a rare occurrence but not impossible. In an ad hoc literature search limited to the period 2003 to 2017, we identified 11 published case reports of preeclampsia developing before 20 weeks' gestation, [28][29][30][31][32][33][34][35][36][37][38] many confirmed by renal biopsy and five of them presenting as HELLP syndrome, an entity with reported median gestational age of 36 weeks at presentation. 39 It has also been suggested that antiphospholipid syndrome may predispose to preeclampsia before 20 weeks' gestation.…”
Section: The Diagnosis Of Preeclampsiamentioning
confidence: 99%